Potential global impacts of alternative dosing regimen and rollout options for the ChAdOx1 nCoV-19 vaccine - Ricardo Aguas (Nature Portfolio, 2021)
The ChAdOx1 nCoV-19 vaccine requires two doses, but under limited supply single dose regimens have also been considered. Here, the authors show using static transmission modelling that under certain conditions it is optimal to more expediently administer a single dose to a larger proportion of the population.